Re-conceptualizing community in risk research. Issue 7 (3rd July 2017) - Paveglio, Travis B.; Boyd, Amanda D.; Carroll, Matthew S.
Abstract : Community is an important concept for determining the factors that influence peoples' perceptions of and actions surrounding risk. However, there are multiple and conflicting definitions for the concept of community and scholars operationalize it in various ways. In this paper, we argue for a renewed focus on community as a guiding consideration in discussions of risk management and the related concepts of resilience, vulnerability, and adaptive capacity. We outline classic and current conceptions of community to articulate how its conceptualization in ongoing risk research might lead to different outcomes, foci, or recommendations about collective adaptation. This includes a discussion of how historic and emerging methodological approaches for studying risk make implicit choices about what community is or how it influences collective response. We close by providing a set of potential axioms that can help researchers better integrate the complexity of community into studies of risk and understand how populations respond to it. Better integrating community into studies of risk could promote policies and communication that are tailored to the unique local context of diverse populations. Such tailoring is more likely to promote adoption of risk mitigations among local populations and perpetuate adaptation as a part of local culture. We contend that a more holistic and systematic approach to documenting local context better encompasses the variable influences that community can have on collective ability to respond to risks.